Hepatogastroenterologists' knowledge of inactive carriers and immunotolerant hepatitis B virus patients in France: results of a practice survey. Issue 5 (May 2015) - Causse, Xavier; Cadranel, Jean-François; Potier, Pascal; Hanslik, Bertrand; Denis, Jacques; Renou, Christophe; Delasalle, Patrick
Abstract : Background: Before the 2012 revision of the EASL guidelines for the management of hepatitis B virus infection, we conducted a survey to determine how French nonacademic hepatogastroenterologists defined inactive hepatitis B virus carriers and immunotolerant patients. Methods: We asked 680 hepatogastroenterologists to complete a simple survey consisting of 11 multiple-choice questions. Results: The participation rate was 32%. HBeAg positivity was not identified as a key criterion for the diagnosis of immunotolerance by 61.9% of the respondents. A total of 82.5 and 75.9% of the respondents identified repeatedly normal alanine transaminase levels and repeatedly low viremia (<2000 IU/ml), respectively, as relevant criteria for the HBsAg inactive carrier state. The question on the biological monitoring of inactive carriers and immunotolerant patients was answered by 78% of the respondents, 97% of whom considered determinations of α-fetoprotein concentration and viremia every 6 ( n =58, 35%) or 12 months ( n =105, 63%) to be useful. Overall, 19% of the respondents declared never having treated an immunotolerant patient; 81% reported that they had treated such patients under some circumstances: 73% before immunosuppression or chemotherapy, 54% treated pregnant women in their third trimester when viremia was greater than 7 log IU/ml, 49% treated health professionals to prevent contamination, and 31% before medically assisted procreation. Conclusion: The definition of 'inactive carrier state' seems to have been well assimilated, but immunotolerance remains poorly understood. Biological monitoring was frequently carried out for inactive carriers and immunotolerant patients, but the diversity of the responses obtained highlights the lack of clear recommendations for the follow-up of these populations.